What Is Being Reported About Vaginal "Lasers"?: An Examination of Adverse Events Reported to the Food and Drug Administration on Energy-Based Devices. (26th July 2021) - Burkett, Linda; Moalli, Pamela; Ackenbom, Mary
Abstract: Background: A description of energy-based genitourinary non-surgical devices (energy-based devices) safety data is outlined given their rapid adoption. Objectives: The authors sought to describe adverse events for energy-based devices in the Manufacturer and User Facility Device Experience database and to compare with similar devices and other subspecialty applications. We hypothesized that products with genitourinary applications had similar adverse events to dermatologic or general surgery applications. Methods: The authors used Reed Tech Navigator to compile adverse events reports for all registered energy-based devices. Individual adverse events reports associated with (1) non-ablative, (2) fractionated, (3) unfractionated, (4) radiofrequency, and (5) hybrid laser technologies were categorized. Adverse event characteristics were compared among genitourinary applications (n = 39) and other subspecialty applications within the same devices (n = 79). Results: Eighteen manufacturers were identified, which collectively manufacture 43 products with genitourinary applications. Thirty-nine genitourinary adverse events were reported and isolated to 6 manufacturers with 11 products, of which 82% (n = 32) were injuries, 15% (n = 6) were device malfunction, and 3% (n = 1) were related to improper maintenance. Local treatment reactions were the most commonly reported injury (62%, n = 21). Adverse events varied by device type, with CO2 lasers having more burns and radiofrequency devices having higher rates of sensation loss. Comparing similar technology types, genitourinary energy-based devices had the fewest adverse events reports per device in the Manufacturer and User Facility Device Experience database. Conclusions: Adverse events were reported for one-quarter of the products currently available, and most were local treatment reactions. The reporting of adverse events is equal to that of other subspecialties, suggesting similar risk profiles. Improved reporting is needed to fully evaluate the safety of individual energy-based devices. Level of Evidence: 4: